The Effect of Quran Memorization on Mathematical Understanding Ability with Pearson Correlation and Linear Regression - Jalaludin, Paiz; Nuraini, Ani; Amigo, Royyan; Jahrani, Siti; Hamdi At-Taibi, Faisal (Department of Mathematics Education University of Muhammadiyah Malang, 2024)
The benefit of memorizing the Quran trigger Islamic education mobilizers to integrate Quran memorization activities as one of the compulsory or extracurricular subjects in formal educational institutions.. This study aims to understand the relationship and influence of the Quran memorization index on students' mathematical abilities. The methods used to answer this problem are the Pearson correlation test and the simple linear regression test. Both statistical methods were rigorously reviewed in this study. The results of this study show that there is a significant relationship between the variable of the Quran memorization index and the mathematical understanding abilities of students at Pondok Pesantren Al-Hasanah Darunnajah 9 with a correlation coefficient of 0.428 which is included in the medium category. In addition, the results showed that there was a positive and significant influence between the Quran memorization index on students' mathematical abilities, where students' mathematical abilities were 18.3% influenced by the Quran memorization index, while the rest were influenced by other factors.